The art of theft [large type] - Thomas, Sherry (Sherry M.) (Thomas, Sherry (Sherry M.). Lady Sherlock series., 2019)
"As "Sherlock Holmes, consulting detective," Charlotte Holmes has solved murders. But she has never stolen a priceless artwork--or rather, made away with the secrets hidden behind a much-coveted canvas. But Mrs. Watson is desperate to help a friend recover those secrets and Charlotte finds herself involved in a scheme to infiltrate a glamorous Yuletide ball where the painting is one handshake away from being sold and the secrets a bare breath from exposure. But nothing about this adventure is what it seems and disaster is biding time on the grounds of a glittering French chateau, waiting for Charlotte to make a single mistake."--Provided by publisher.